L’empire du nucléaire : quand Fukushima ne crachait pas encore ses « atomes pour la paix » - Thierry Ribault (Ebisu: Études Japonaises, 2012)
Japan’s nuclear policy has long been tied to American foreign policy, especially in the context of anticommunist ideology and the Cold War. The civil use of nuclear energy in Japan is an offshoot of America’s military use, a fact that allows us to understand how one of the most earthquake-prone countries in the world was destined to become the third largest user of nuclear power in the world. The use of nuclear energy is directly linked to the propagation of the doctrine espoused by Dwight D. Eisenhower in his ”Atoms for Peace” speech delivered on 8 December 1953 before the United Nations Assembly.